VIOLATED MAXIM IN THE AMAZING SPIDER-MAN 2 MOVIE - Sofa Priyandayani Nasution and Siti Aisah Ginting (LINGUISTICA, 2015)
This study is concerned with an analysis of Grice’s Cooperative Principles whichare constituted in a conversation. This research was conducted by usingqualitative method. The analysis particularly discusses the violation of maxim inthe utterances, which are described in four types. They are the maxim of quantitymaxim of quality, maxim of relation and maxim of manner. The data of this studyare the utterances of the main character in The Amazing Spider-Man 2 movie. Theutterances which contain violated maxim are identified and analyzed. Thefindings show that there are 51 utterances violation of maxim in The AmazingSpider-Man 2 movie. Those are 20 utterances (39.2%) violation of maxim relationand it can be concluded as the dominat type violated, 16 (31.5%) for maxim ofquantity as the second largest number violated and 8 (15.6%) for the maxim ofquality. The last, those are 7 utterances (13.7%) violated maxim of manner. Itshows that the maxim of manner is the lowest number. Based on the analysis,there are the reasons as the main backgrounds which prompt the main characternamed Peter Parker to violate the maxims. The reason are to keep the secret andchange the topic.